Epitope spreading in animal models: array of hope in rheumatoid arthritis and multiple sclerosis. - Lundberg, K; Venables, P (2008)
The paradigm for pathogenic autoimmunity is the generation of high-titre, affinity-matured autoantibodies to a restricted family of autoantigens, in the appropriate genetic context. Genetic determinants of autoimmunity are largely found within the major histocompatibility complex (MHC) and the 'genotype to serotype to phenotype' concept is supported in a number of autoimmune diseases, where both genotype and serotype are well established. The serotype is autoantigen-driven, with evidence of epitope spreading as the disease evolves from asymptomatic to pathogenic autoimmunity. In rheumatoid arthritis and multiple sclerosis, where the autoantigens are poorly characterised, the use of an array in animal models may produce a hint of what happens in human disease. A more complete picture will be obtained from animals transgenic for human MHC, immunised with known human autoantigens.